Impact of Andrographolide and Melatonin Combinatorial Drug Therapy on Metastatic Colon Cancer Cells and Organoids. (June 2021) - Sharda, Neha; Ikuse, Tamaki; Hill, Elizabeth; Garcia, Sonia; Czinn, Steven J; Bafford, Andrea; Blanchard, Thomas G; Banerjee, Aditi
Background: The death rate (the number of deaths per 100 000 people per year) of colorectal cancer (CRC) has been dropping since 1980 due to increased screening, lifestyle-related risk factors, and improved treatment options; however, CRC is the third leading cause of cancer-related deaths in men and women in the United States. Therefore, successful therapy for CRC is an unmet clinical need. This study aimed to investigate the impacts of andrographolide (AGP) and melatonin (MLT) on CRC and the underlying mechanism. Methods: To investigate AGP and MLT anticancer effects, a series of metastatic colon cancer cell lines (T84, Colo 205, HT-29, and DLD-1) were selected. In addition, a metastatic patient-derived organoid model (PDOD) was used to monitor the anticancer effects of AGP and MLT. A series of bioassays including 3D organoid cell culture, MTT, colony formation, western blotting, immunofluorescence, and quantitative polymerase chain reaction (qPCR) were performed. Results: The dual therapy significantly promotes CRC cell death, as compared with the normal cells. It also limits CRC colony formation and disrupts the PDOD membrane integrity along with decreased Ki-67 expression. A significantly higher cleaved caspase-3 and the endoplasmic reticulum (ER) stress proteins, IRE-1 and ATF-6 expression, by 48 hours were found. This combinatorial treatment increased reactive oxygen species (ROS) levels. Apoptosis signaling molecules BAX, XBP-1, and CHOP were significantly increased as determined by qPCR. Conclusions: These findings indicated that AGP and MLT associated ER stress-mediated apoptotic metastatic colorectal cancer (mCRC) cell death through the IRE-1/XBP-1/CHOP signaling pathway. This novel combination could be a potential therapeutic strategy for mCRC cells.